2007
DOI: 10.1007/s11113-007-9022-0
|View full text |Cite
|
Sign up to set email alerts
|

Residential independence among older persons: community and individual factors

Abstract: The objective of this study is to evaluate an expanded version of the resource model of living arrangements among older persons. This expanded model includes community-level measures of geriatric health services and housing market conditions. We employ the first two waves of the National Survey of Families and Households to test static and longitudinal fixed effects models of residential living arrangements. We find that residing in areas with higher levels of geriatric health care services increases the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
6
22
0
1
Order By: Relevance
“…Besides the factors described above, many other factors also infl uence elders' living arrangements, 2 such as health and functional status (Burr & Mutchler, 2007 ;Sarma et al, 2009 ;Waite & Hughes, 1999 ), availability and proximity of adult children or others for co-residence (Cameron, 2000 ;Glick & Van Hook, 2002 ), community factors including housing supply and health care facilities (Burr & Mutchler, 2007 ), and other factors.…”
Section: Elderly Adults' Living Arrangementsmentioning
confidence: 99%
“…Besides the factors described above, many other factors also infl uence elders' living arrangements, 2 such as health and functional status (Burr & Mutchler, 2007 ;Sarma et al, 2009 ;Waite & Hughes, 1999 ), availability and proximity of adult children or others for co-residence (Cameron, 2000 ;Glick & Van Hook, 2002 ), community factors including housing supply and health care facilities (Burr & Mutchler, 2007 ), and other factors.…”
Section: Elderly Adults' Living Arrangementsmentioning
confidence: 99%
“…North American studies have found that elder dependency is often the result of a physical or mental disability that prevents the ailing individual from living alone (Burr and Mutchler 2007). Elder parents are also more likely to live with adult children in larger families.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that persons with greater economic resources, more children, and better functional status are more capable of maintaining independence and less likely to die or live in a nursing home. Such evidence shows the utility of micro-level approaches to understanding community living arrangements (Burr and Mutchler 2007).…”
Section: Literature Reviewmentioning
confidence: 88%